Regulation of cell dynamics by rapid integrin transport through the biosynthetic pathway - Lerche, Martina; Mathieu, Mathilde; Hamidi, Hellyeh; Chastney, Megan; Jacquemet, Guillaume; Bruininks; Bart Marlon Herwig; Kaptan, Shreyas; Malerød, Lene; Pedersen, Nina Marie; Brech, Andreas; Matoba, Nobuyuki; et al. (Rockefeller University Press, 2026)
Constitutive integrin endocytosis and recycling control cell movement and morphology. In contrast, the role of newly synthesized integrins delivered via the biosynthetic pathway has been largely overlooked. We used the retention using selective hooks system to monitor the localization of new integrins exiting the endoplasmic reticulum in space and time. We discovered that new integrin delivery to the plasma membrane is polarized and enhances cell protrusion and focal adhesion growth in an extracellular matrix-ligand–dependent manner. Motor-clutch modeling explained the increased adhesion as higher integrin availability driving recruitment of additional receptors. Unexpectedly, live-cell imaging revealed a small subset of fast-emerging integrin vesicles rapidly transported to the cell surface to facilitate localized spreading. This unconventional secretion depended on cell adhesion and correlated with increased surface levels of immature, high-mannose glycosylated integrin, indicating bypass of the canonical Golgi-dependent secretory pathway. Thus, spatial plasma membrane-targeting of new integrins rapidly alters adhesion receptor availability, providing cells with added plasticity to respond to their environment.